2014
DOI: 10.1371/journal.pone.0108285
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Essential Oils on Aspergillus ochraceus Growth and Ochratoxin A Production

Abstract: Ochratoxin A (OTA) is a mycotoxin which is a common contaminant in grains during storage. Aspergillus ochraceus is the most common producer of OTA. Essential oils play a crucial role as a biocontrol in the reduction of fungal contamination. Essential oils namely natural cinnamaldehyde, cinnamon oil, synthetic cinnamaldehyde, Litsea citrate oil, citral, eugenol, peppermint, eucalyptus, anise and camphor oils, were tested for their efficacy against A. ochraceus growth and OTA production by fumigation and contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 39 publications
7
81
0
1
Order By: Relevance
“…In contrast with these results, Hua and coworkers (23) reported that the essential oil of cinnamon inhibits the growth of A. ochraceus and OTA production. In a related study, Ferreira (24) found that turmeric has inhibitory effect on mycotoxin production.…”
Section: Discussionmentioning
confidence: 72%
“…In contrast with these results, Hua and coworkers (23) reported that the essential oil of cinnamon inhibits the growth of A. ochraceus and OTA production. In a related study, Ferreira (24) found that turmeric has inhibitory effect on mycotoxin production.…”
Section: Discussionmentioning
confidence: 72%
“…The absence of OTA noticed in clove samples could be related to the antifungal activity of this spice. Mostafa et al (1990) and Hua et al (2014) observed the inhibitory effect of clove on fungal growth and OTA production. The absence of OTA in clove has also been reported by Karan et al (2005) in clove sold at Belgrade, Serbia.…”
Section: Discussionmentioning
confidence: 97%
“…The fungitoxicity of oil extracted from caraway (Carum carvi) against A. flavus and A. parasiticus was also reported by Soher (1999). Hua et al (2014) have reported the inhibition of A. ochraceus, A. flavus, A. parasiticus and F. moniliforme by the essential oil of thyme, cinnamon, anise spearmint and basil oil at 3000 ppm. Cinnamon oil was also reported to be fungistatic against mycotoxigenic fungi studied by Mukherjee and Nandi (1994) and found the useful in protecting concentration to the extent of 97% OTA and 75% of the biomass production by P. nordicum.…”
Section: Resultsmentioning
confidence: 99%
“…In recent times, considerable interest in the essential oils as in the prevention of mycotoxins in foods and feeds has been witnessed (Hua et al, 2014). Basil oil inhibited the growth of the F. verticillioides, F. oxysporum, F. proliferatum and F. subglutinans (Kocic-Tanackov et al, 2013).…”
Section: Introductionmentioning
confidence: 99%